Effects of intravenous administration of caffeine on physiologic variables in exercising horses - Ferraz, Guilherme C. [UNESP]; Teixeira Neto, Antônio Raphael [UNESP]; Mataqueiro, Maria I. [UNESP]; Lacerda-Neto, Jose C. [UNESP]; Queiroz-Neto, Antonio [UNESP] (Amer Veterinary Medical Assoc, 2008)
Objective-To investigate the effect of acute administration of caffeine on the athletic performance of Arabian horses.Animals-12 healthy adult Arabian horses that were trained for exercise on a treadmill.Procedures-By use of a crossover study design, horses received each of the following treatments: IV administration of caffeine (5 mg/kg) and IV administration of approximately the same volume of saline (0.9% NaCl) solution. Order of treatment was randomized, and there was a 10-day interval between treatments. Thirty minutes after treatments, horses underwent an incremental exercise test (IET) on a treadmill. Blood samples were collected 15 seconds before the end of each velocity step of the IET for determination of blood lactate, blood glucose, plasma cortisol, and plasma insulin concentrations. Heart rate and hematologic variables were also analyzed.Results-Velocities achieved when heart rates were 180 and 200 beats/min increased Significantly in caffeine-treated horses, compared with control horses. Velocities corresponding to blood lactate concentrations of 4 and 2 mmol/L decreased significantly in caffeine-treated horses, compared with control horses. In comparison between groups, insulinemia was greater in control horses and glycemia was greater in caffeine-treated horses. Plasma cortisol concentration was significantly lowered by treatment with caffeine.Conclusions and Clinical Relevance-IV administration of caffeine at 5 mg/kg improved the performance of Arabian horses during intense exercise of short duration and diminished the oxidative metabolism of glucose. (Am J Vet Res 2008;69:1670-1675)